The impact of human rights law on armed forces - Rowe, P. J. (Peter J.) (Cambridge University Press, 2006)
"This is a timely study in light of the allegations of ill-treatment by soldiers of civilians following the war in Iraq and the detention of 'unlawful combatants' in Guantanamo Bay. It will have broad appeal, for scholars and students in human rights, international law and military studies, and anyone concerned with policy relevant to the armed forces."--Jacket